Doping Engineering of M‐N‐C Electrocatalyst Based Membrane‐Electrode Assembly for High‐Performance Aqueous Polysulfides Redox Flow Batteries - Bixian Chen; Huan Huang; Jiande Lin; Kailing Zhu; Le Yang; Xiang Wang; Jiajia Chen (Advanced Science, 2023)
Abstract Polysulfides aqueous redox flow batteries (PS‐ARFBs) with large theoretical capacity and low cost are one of the most promising solutions for large‐scale energy storage technology. However, sluggish electrochemical redox kinetics and nonnegligible crossover of aqueous polysulfides restrict the battery performances. Herein, it is found that the Co, Zn dual‐doped N‐C complex have enhanced electrochemical adsorption behaviors for Na2S2. It exhibits significantly electrochemical redox activity compared to the bare glassy carbon electrode. And the redox reversibility is also improved from ΔV = 210 mV on Zn‐doped N‐C complex to ΔV = 164 mV on Co, Zn‐doped N‐C complex. Furthermore, membrane‐electrode assembly (MEA) based on Co, Zn‐doped N‐C complex is firstly proposed to enhance the redox performances and relieve the crossover in PS‐ARFBs. Thus, an impressively high and reversible capacity of 157.5 Ah L−1 for Na2S2 with a high capacity utilization of 97.9% could be achieved. Moreover, a full cell PS‐ARFB with Na2S2 anolyte and Na4[Fe(CN)6] catholyte exhibits high energy efficiency ≈88.4% at 10 mA cm−2. A very low capacity decay rate of 0.0025% per cycle is also achieved at 60 mA cm−2 over 200 cycles.